Third time lucky: An analysis of Paris’ bids for the Olympic Games in 2008, 2012 and 2024 - Jastrząbek, Julia (Research Papers in Economics and Finance, 2023)
Hosting the Olympic Games has become a unique occasion to implement several projects aimed at upgrading public infrastructure and improving the economic performance of the host city. Thus, some cities are so determined to host the Olympics that they decide to bid multiple times. One of the examples of such a city is Paris, which since the 2000s has submitted its bids three times, for 2008, 2012, and 2024, of which the last attempt turned out to be successful. Based on the above, the main aim of this article is to present the trajectory of changes and developments made by the three successive bid attempts, with an emphasis on the latest successful campaign. This study demonstrates that there are some recurrent ideas, projects, and plans shared by each bid with some modifications to emphasize their uniqueness, novelty, and up-to-date approach. In some aspects, the Paris 2024 bid builds on its previous candidature from 2012 in the field of long-term legacy effects and sustainability. Therefore, there is a consistent action taken by the bid managers and city authorities in terms of using the Olympic Games as a tool for urban regeneration and sports development.